Study of Paired Approach Wake Separation Based on Crosswinds - Weijun Pan; Yanqiang Jiang; Junjie Zhou; Wei Ye; Yuqin Zhang (Aerospace, 2024)
The effect of crosswinds on paired approach (PA) procedures for Closely Spaced Parallel Runways (CSPR) is investigated in this paper by fully utilizing the crosswind environment to implement a more efficient PA and increase runway capacity. An improved wake dissipation model is used to quickly predict the change in the wake velocity field for the PA procedures. The change in the width of the hazard zone is explored in detail using the roll moment coefficient as a determination index. The calculation method for the hazard zone of a wake encounter in a PA is designed considering the influence of crosswind, turbulence, and ground effect. The results show the diffusion rate of the hazard zone and a decrease in the width of the maximum hazard zone under a breezeless environment with increases in the turbulence intensity. The maximum hazard zone width decreases with an increase in crosswind speed. Favorable crosswinds can reduce wake separation and improve the efficiency of a PA. Lower turbulence intensity has a better crosswind effect under a normal PA. The 3-degree offset PA can accommodate larger unfavorable crosswinds, with a higher turbulence intensity having a better crosswind effect. The 3-degree offset PA can substantially increase the proportion of time when no wake affects the PA procedure.